Postoperative Pharyngolaryngeal Adverse Events with Laryngeal Mask Airway (LMA Supreme) in Laparoscopic Surgical Procedures with Cuff Pressure Limiting 25 cmH2O: Prospective, Blind, and Randomised Study. (17th March 2014) - Kang, Joo-Eun; Oh, Chung-Sik; Choi, Jae Won; Son, Il Soon; Kim, Seong-Hyop
Abstract : To reduce the incidence of postoperative pharyngolaryngeal adverse events, laryngeal mask airway (LMA) manufacturers recommend maximum cuff pressures not exceeding 60 cmH2 O. We performed a prospective randomised study, comparing efficacy and adverse events among patients undergoing laparoscopic surgical procedures who were allocated randomly into low (limiting 25 cmH2 O, L group) and high (at 60 cmH2 O, H group) LMA cuff pressure groups with LMA Supreme. Postoperative pharyngolaryngeal adverse events were evaluated at discharge from postanaesthetic care unit (PACU) (postoperative day 1, POD 1) and 24 hours after discharge from PACU (postoperative day 2, POD 2). All patients were well tolerated with LMA without ventilation failure. Before pneumoperitoneum, cuff volume and pressure and oropharyngeal leak pressure (OLP) showed significant differences. Postoperative sore throat at POD 2 (3 versus 12 patients) and postoperative dysphagia at POD 1 and POD 2 (0 versus 4 patients at POD 1; 0 versus 4 patients at POD 2) were significantly lower in L group, compared with H group. In conclusion, LMA with cuff pressure limiting 25 cmH2 O allowed both efficacy of airway management and lower incidence of postoperative adverse events in laparoscopic surgical procedures. This clinical trial is registered with KCT0000334 .